Analisis Abnormal Return dan Trade Volume Acivity Sebelum dan Sesudah Pengumuman Kebijakan Restrukturisasi Kredit Pandemi Covid-19 - Nadia Nur Azmi; Ruhadi Ruhadi; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study is to find out abnormal return and trade volume activity before and after the announcement of the covid-19 pandemic credit reconstructuralization policy (a study of banking companies listed on the Indonesia Stock Exchange). Quantitative research with population is a company that is a member of the Indonesia Stock Exchange and is used as many as 44 companies from the financial services sector of banking subsectors listed on the Indonesia Stock Exchange as a sample. Sampling techniques use purposive sampling from secondary data taken from idx.co.id and yahoo finance pages. Data analysis techniques use descriptive statistical analysis, classical assumption tests and other tests (Wilcoxon Signed-Rank Test). The results showed significant differences in Abnormal Return (AR) and Trade Volume Activity (TVA) before and after the announcement of the Covid-19 pandemic credit restructuring policy.